Comparative Analysis of Government Website and Service Monitoring System Ratings among State Islamic Religious Councils (SIRCs) in Malaysia - Mohd Ali, Nor Aishah; Abdullah, Zaharah; Minhad, Siti Fatimah Noor; Ahmad, Khairiah; Kasim, Eley Suzana; Ahamad Nawawi, Nurul Hidayah (Information Management and Business Review, 2024)
This study explores the comparison of websites of various State Islamic Religious Councils (SIRCs) in Malaysia using the Government Website and Service Monitoring System known as SPLaSK ratings. SPLaSK, an initiative by the Malaysian government serves as a critical tool for monitoring and evaluating the performance of government websites and services. By focusing on the SIRCs, this study seeks to identify patterns, strengths, and areas for improvement in digital governance. Using qualitative content analysis and semi-structured interviews, the study analyzes SPLaSK ratings of SIRCs to understand how these councils utilize digital platforms to engage with the public, disseminate information, and provide services. Websites registered with SPLaSK are assessed based on six (6) dimensions, namely accessibility, ease of use, quality of content, privacy or security, responsiveness, and reliability. It has been disclosed that only 10 out of 14 SIRCs were registered with SPLaSK in 2023, with 40% achieving excellent ratings of above 80%. The overall scores of the websites also suggest that four (4) SIRCs have underperformed, receiving scores below 50, attributed to inefficient website management. The findings offer valuable insights into the effectiveness of SPLaSK in promoting transparency, efficiency, and user-friendliness in government digital services, thus contributing to the broader discourse on digital governance within government agencies in Malaysia